2002
DOI: 10.1007/s00429-002-0252-y
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of elastic tissue fibres in stem villus blood vessels of the human placenta during IUGR and IUGR with concomitant pre-eclampsia

Abstract: In a recent study we described an increase of elastic tissue fibres in blood vessel walls of placental stem villi during pre-eclampsia when compared to uncomplicated pregnancies. Furthermore, the thickness of these blood vessel walls was enhanced in pre-eclampsia. Since it is known that elastic tissue fibres increase in systemic hypertension, it may be assumed that the enhancement of elastic tissue fibres in placental stem villi during pre-eclampsia may be induced by the hypertension. To get further insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…bcl-2 and p53 (16,17,31), and histopathologic changes including alterations in stem villus blood vessels and elongated terminal villi (18,32,33). Two mechanisms have been proposed to explain these observations.…”
Section: Discussionmentioning
confidence: 99%
“…bcl-2 and p53 (16,17,31), and histopathologic changes including alterations in stem villus blood vessels and elongated terminal villi (18,32,33). Two mechanisms have been proposed to explain these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant FGR is caused by reduced fetal growth resulting from maternal conditions such as undernutrition, smoking, drugs, and prepregnancy or pregnancy diseases, that include chronic hypertension or preeclampsia (8). Although the etiology and pathophysiology of FGR may be varied (2), it is widely accepted that poor placental development and or placental disease is the major common factor that is associated with abnormal fetal growth (8,9). Once congenital infection and chromosomal or congenital anomalies have been ruled out, FGR is mostly a result of uteroplacental insufficiency (10).…”
Section: Introductionmentioning
confidence: 99%
“…Wilhelm et al. 12 observed a greater thickness in stem villi vessel walls associated with a greater quantity of elastic fiber in patients with pre‐eclampsia. These findings were attributed to an increase in maternal and/or fetal blood pressure, accompanied by stem villi wall damage responsible for the proliferation and activation of smooth muscular cells, which possess a great response capacity to physiological and pathological stress.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in placental stem villi walls are observed in patients with diabetes, Rh-immunization, stillborns and maternal hypertension, which may reflect a fetal hemodynamic response, represented by an increase in fetal blood pressure in response to low blood flow. 11 Wilhelm et al 12 observed a greater thickness in stem villi vessel walls associated with a greater quantity of elastic fiber in patients with pre-eclampsia. These findings were attributed to an increase in maternal and/or fetal blood pressure, accompanied by stem villi wall damage responsible for the proliferation and activation of smooth muscular cells, which possess a great response capacity to physiological and pathological stress.…”
Section: Discussionmentioning
confidence: 99%